Evaluation of the efficacy of 50% citric acid solution in plane wart treatment - Vali Anahita; Ferdowsi Faezeh (Wolters Kluwer Medknow Publications, 2007)
Background and Aims: Treatment of plane warts is problematic, methods such as cryotherapy and cauterization is associated with high recurrence rate, risk of scar, pain and high cost. Topical tretinoin causes irritant contact dermatitis that limited its use. Citric acid was used in treatment of warts in traditional medicine of Iran. We evaluated the efficacy of 50% citric acid solution in water in treatment of plane warts and compared it with 0.05% tretinoin lotion. Materials and Methods : This study was a double blind; prospective, case-control study.Seventy-five patients with bilateral plane warts who signed informed consent were included. Exclusion criteria were pregnancy, breast-feeding, suffering from any systemic disease and the use of any other drug due to treatment of warts in past six weeks. The patients randomly used citric acid or Tretinoin lotion to lesions at each side of the body. Randomization was performed by coin-flipping. Patients were examined at three weeks interval for six weeks and number of warts were recorded in the proforma, which included the name, sex, address and code of the drug that was used in each side of the body and side effects. The results were analyzed by Chi-square test statistically. Results: After six weeks 64.4% of the lesions in citric acid treated group disappeared versus 53.7% of the lesions in tretinoin treated group. This difference was significant ( P value<o.o5, CI=95%). 45.5% of patients were at second decade (11-20 years). Incidence of irritant contact dermatitis with application of tretinoin was 22% versus 14.7% with citric acid. Conclusion: On the basis of this study, the treatment of plane warts by 50% citric acid is strongly suggested. This modality is superior to tretinoin lotion due to higher efficacy and low incidence of side-effects and lower cost.